Integrasi Pembelajaran Pendidikan Agama Islam Dengan Gerakan Pramuka Dalam Meningkatkan Altruistik Peserta Didik - Irfan Kuncoro (Thawalib: Jurnal Kependidikan Islam, 2020)
This research is motivated by the not yet achieving the massive goals of education, especially being faithful, pious and noble. The decadence of altruism can be seen in MA Sunan Pandanaran, an example of which is apathy among students. The solution is to "Strengthen Altruism" through the Scout Movement at the base of MA Sunan Pandanaran. This type of research is descriptive qualitative, the sampling of data sources was done by purposive and snowball. Data collection techniques using documentation, observation, and interviews. By taking data sources from PAI educators, scout coaches and scout members, as well as the implementation of PAI learning, and scouting that has been programmed by MA Sunan Pandanaran scouts. Furthermore, it is analyzed using data analysis methods by Miles Huberman. Then test the validity of the data using triangulation of sources and techniques. The results of this study indicate: First, the implementation of the curriculum used by the base is the integration of Islamic Education and General Skills Requirements. Second, the Scouting at the base is going well, through a planned work program. Third, the linkage between Scouting and Altruism at the base lies in the Scout Movement's code of honor which is applied through Islamic education and scouting. Fourth, the implementation of scouting activities that strengthen the altruistic spirit at the base lies in Dasa Darma and Tri Satya which are applied with PAI education and scouting which is carried out regularly.